Investation of Ectoparasites In Chickens In Village of Kramat District of Bangkalan Regency of Bangkalan - Fania Selfiannisa; Suherni Susilowati; Poedji Hastutiek; Lucia Tri Suwanti; Kusnoto Kusnoto; Agus Sunarso (Universitas Airlangga, 2018)
A study on the infestation of ectoparasites in chicken’s raised in Village of Kramat, District of Bangkalan, Regency of Bangkalan was conducted between July to October 2017. A total of 60 chickens were examined based on their sex and region of the chicken’s body. Identification was carried out on ectoparasites found identified using permanent mounting methods and scraping. The types of ectoparasites were M. gallinae 77%, L. caponis 52%, M. stramineus 15%, R. sanguineus 3%, G. gallinae 2%, G. gigas 2%, and D. gallinae 2%. Data were analyzed using Chi Square and Correspondence. The results of infestation was higher in males than females, although the difference was not statistically significant (P>0.05). Results of analysis of the pattern of investation of ectoparasites in the region that includes in males and females body are M. gallinae in the region of the back. L. caponis in the region of the wings. M. stramineus. R. sanguineus in the region of the head-neck, G. gigas in the region of belly, G. gallinae in the region of the leg just found in the males body. D. gallinae in the region of the leg just found in the females body.